Variation in Actinobacterial Community Composition and Potential Function in Different Soil Ecosystems Belonging to the Arid Heihe River Basin of Northwest China - Zhang, Binglin; Wu, Xiukun; Tai, Xisheng; Sun, Likun; Wu, Minghui; Zhang, Wei; Chen, Ximing; Zhang, Gaosen; Chen, Tuo; Liu, Guangxiu; Dyson, Paul (Frontiers in Microbiology, 2019)
Actinobacteria are known for their metabolic potential to produce diverse secondary metabolites such as antibiotics. Actinobacteria also play important roles in biogeochemical cycling and how soils develop. However, little is known about the effect of vegetation type on Actinobacterial community structures in soils from arid regions. For these reasons, we have analysed the Actinobacterial communities of five types of ecosystem (tree grove, shrub, meadow, desert and farm) in the Heihe river basin. Using 16S rRNA high-throughput sequencing, we found 11 classes of Actinobacteria and the dominant classes were the Actinobacteria (36.2%), Thermoleophilia (28.3%), Acidimicrobiia (19.4%). 5 classes, 15 orders, 20 families and 36 genera were present in all samples. The dominant generalist genera were Gaiella, Solirubrobacter, Nocardioides, Mycobacterium and Pseudonocardia. The Actinobacterial community structures were significantly affected by the environment and vegetation type. The diversity of the Actinobacterial community in the desert ecosystem was high, and this ecosystem harboured the highest proportion of unclassified sequences, representing rare actinobacteria. Functional metagenomic prediction, using PICRUSt, indicated that Actinobacteria play an important role in nitrogen cycling in both desert and cultivated farm ecosystems.